180 The Efficacy of Amoxapine for Ejaculatory Dysfunction. (1st May 2022) - Watanabe, A.; Kitamura, H.
ABSTRACT: Introduction: Amoxapine, as a tricyclic antidepressant, inhibits noradrenalin reuptake and is often used in the treatment for retrograde ejaculation in Japan. Objective: To evaluate the efficacy of amoxapine for ejaculatory disorder in our hospital, retrospectively. Methods: Seventeen men (age 38.4 ± 5.2 y) complaining with infertility or decrease of ejaculated semen volume who received amoxapine (25-75 mg/day) for retrograde ejaculation or emission less were included. The changes of semen analysis parameters before and after amoxapine therapy were examined. When the semen volume increased after therapy, it was considered to be effective. Wilcoxson signed-ranks test was used for statistical analysis. P < 0.05 was considered to be significant. This study was approved by the ethical committee of Toyama university hospital. Results: It was diagnosed retrograde ejaculation in 15 patients (complete type 3, partial type 12 cases), and emission less in two patients. The causes of ejaculatory disorders were diabetes mellitus in 4 patients, urethral trauma in 1 patient, antidepressants in 1 patient, anti-androgenetic alopecia drugs in 1 patient, sigmoidectomy for dolichocolon and proctopexy for rectal prolapse in 1 patient, and unknown cause in 9 patients. The average value of BMI in patients was 25.0 ± 4.18. Each patient had normal level of the total testosterone in blood. The average score of International Index of Erectile Function score and Erection hardness score before treatment showed 49.8 ± 17.9, 3.13 ± 0.62, respectively. The efficacy rate of amoxapine was 78.6%. Before and after amoxapine therapy, semen volume increased significantly from 0.29 ± 0.31 ml to 1.23 ± 1.56 ml, sperm concentration did from 19.5 ± 34.7 × 10 6 /ml to 99.3 ± 172.7 × 10 6 /ml, and total sperm count did from 7.83 ± 14.0 × 10 6 to 94.8 ± 149.7 × 10 6, respectively. By the amoxapine therapy, the antegrade ejaculated sperm count ratio* significantly increased from 28.1 ± 37.6 to 65.7 ± 40.1%. The average duration of amoxapine therapy was 13.0 ± 20.6 months and the maximum duration was 80 months. No side effects were observed. Of all patients, 15 patients would hope to have baby. There were 3 spontaneous pregnancies and 2 pregnancies due to assisted reproductive technology. All 5 pregnancies resulted in delivery. Conclusions: It was suggested that amoxapine is an effective drug for ejaculatory disorder and might not only increase ejaculation volume but also improve sperm concentration and total sperm count. *(total sperm counts in ejaculated semen / (total sperm counts in ejaculated semen + total sperm counts in urine after orgasm)) × 100% Disclosure: Work supported by industry: no.